Gambaran Risiko Dismenore Primer Pada Mahasiwa Tingkat Akhir Universitas ‘Aisyiyah Surakarta - Arinda fitrianatanti; Anjar Nurrohmah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Final-year students completing their final projects often experience anxiety. Risk factors underlying the occurrence of dysmenorrhea include age at menarche, longer than normal menstrual duration, smoking habits, exercise habits, and stress levels. Research Objective: To describe the incidence of dysmenorrhea, age at menarche, menstrual duration, and stress levels among final-year students at Universitas Aisyiyah Surakarta. Method: This study is a quantitative descriptive type using simple random sampling. The study involved 74 respondents meeting the inclusion criteria of final-year female students who have experienced menstruation; exclusion criteria included those willing to participate and not suffering from reproductive organ diseases. Results: Incidence of dysmenorrhea: most respondents experienced dysmenorrhea with mild pain levels, totaling 34 respondents (47.3%). Age at menarche: most respondents experienced menarche at an ideal age, totaling 48 respondents (64.9%). Menstrual duration: most respondents had a normal menstrual duration, totaling 69 respondents (92.2%). Stress levels: most respondents experienced moderate stress, totaling 52 respondents (70.3%). Conclusion: Regarding dysmenorrhea, most respondents experienced mild dysmenorrhea; concerning age at menarche, most respondents had an ideal age; regarding menstrual duration, most respondents had a normal duration; concerning stress levels, most respondents experienced moderate stress.